Successful treatment of open jaw and jaw deviation dystonia with botulinum toxin using a simple intraoral approach. Issue 3 (March 2015) - Moscovich, Mariana; Chen, Zhongxing Peng; Rodriguez, Ramon
Abstract Oromandibular dystonia (OMD) is a focal dystonia that involves the mouth, jaw, and/or tongue. It can be classified as idiopathic, tardive dystonia or secondary to other neurological disorders and subdivided into jaw opening, jaw closing, jaw deviation and lip pursing. The muscles involved in jaw opening dystonia are usually the digastrics and lateral pterygoids. It is known that the lateral pterygoids may be approached both internally and externally. The external approach is the most common; however neurologists experienced in treating patients with botulinum toxin can safely and with no extra cost perform the intraoral procedure. We report our experience in the treatment of jaw opening and jaw deviation dystonia using the intraoral injection approach. Eight patients were selected from the University of Florida with a clinical diagnosis of open jaw/jaw deviation dystonia. All of them were injected with onabotulinum toxin A using the internal approach and the clinical global impression scale was applied. The mean age of the patients was 67 (standard deviation [SD] 10.2) years, with a disease duration of 10.2 (SD 7.7) years and the mean distance they traveled to our institution was 448 km (278 miles). After treatment, six patients scored as very much improved in the clinical global impression scale and two patients scored as much improved. Only one patient reported an adverse event of nasal speech following one of the injections that improved after 4 weeks. Botulinum toxin injections for open jaw/jaw deviation dystonia can be safely performed with the intraoral approach without the need of special devices other than electromyography.